Integrating an ICT carbon calculator tool into procurement processes at De Montfort University: lessons learned. Issue 2 (April 2013) - Bull, Richard; Ozawa-Meida, Leticia; Brockway, Paul; Holland, Carl
Background: This paper presents lessons learnt from a Jisc-funded research project that developed and implemented an information communication technology tool enabling staff to understand the environmental impact of their activities and support sustainable procurement across De Montfort University (Leicester, UK).Results: An environmentally extended input–output calculation approach was adopted to calculate the emissions and a 'dashboard style' approach was used to present the information. While the tool was developed successfully, its institutional impact was limited by numerous barriers.Conclusion: These challenges provided several key learning points: cost remains the main priority in procurement teams much higher than environmental aspects; committed 'champions' are key to organizational change; and information communication technology carbon/sustainability tools need to be an integral part of an organization's existing procurement systems.